The Effect of Inflation, Interest Rate, Exchange Rate and GDP Growth on Stock Price Index: (Property and Real Estate Companies 2017-2021) - Indah Devi Novian Sari; Emmelia Tan (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2023)
The purpose of this research is to examine the forces that will shape the performance of the IDX property and real estate index from 2017 to 2021. Inflation, interest, and exchange rates, as well as GDP growth, are the variables examined. Information gathered from www.idx.co.id, www.bi.go.id, andÂ www.bps.go.id. Stock price index data covering 60 months was gathered for this analysis. In this research, regression analysis using Eviews 11 was employed for data crunching. The Normality, Multicollinearity, Autocorrelation, and Heteroscedasticity tests from the Classical Assumption Test are used in this investigation. The Coefficient of Determination Test (R2), the Partial T Test, and the Simultaneous F Test are all examples of Hypothesis Tests. Inflation was found to have a significant value (0.04040.05), interest rates (0.00210.05), exchange rates (0.00220.05), and gross domestic product (0.00260.05) were all found to be significantly different from zero.